2020
DOI: 10.1111/jgh.15032
|View full text |Cite
|
Sign up to set email alerts
|

Marshall and Warren Lecture 2019: A paradigm shift in pathophysiological basis of irritable bowel syndrome and its implication on treatment

Abstract: Irritable bowel syndrome (IBS), a common functional gastrointestinal disorder (FGID), has often been considered rather inappropriately as psychogenic in the past. Though psychological issues are important comorbidities in a proportion of IBS patients, the evidences are far from enough to label this condition as psychogenic only. In the recent past, evidences are emerging that underscores the concept supporting pure psychogenic theory of IBS and suggest this disorder to be rather microorganic. Accordingly, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 72 publications
(116 reference statements)
2
54
1
6
Order By: Relevance
“…As reported in the literature [3], the authors also found that the female students more often had IBS than male students. Since the authors also found subjects with DGBIs, including IBS, had anxiety and depression more often, the data on these psychological parameters among female and male subjects should be provided.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…As reported in the literature [3], the authors also found that the female students more often had IBS than male students. Since the authors also found subjects with DGBIs, including IBS, had anxiety and depression more often, the data on these psychological parameters among female and male subjects should be provided.…”
supporting
confidence: 68%
“…Overlap FGIDs are known to be associated with more severe disease, poorer quality of life, consultation behavior, psychological comorbidity, and an unsatisfactory response to treatment in comparison to a single disorder [3]. However, the authors did not provide the data on the frequency and mean or median (with standard deviation or range) scores of Hamilton anxiety and depression rating scales of subjects with single compared to overlap FGIDs.…”
mentioning
confidence: 99%
“…Zu langfristigen Darmbeschwerden nach radikaler Zystektomie gibt es wenig validierte Daten, entsprechend liegen auch speziell für diese Situation keine evidenzbasierten Empfehlungen für eine mögliche Therapie vor. Ein möglicher Ansatz ist es bei den Patienten, die durch funktionelle Darmbeschwerden belastet sind, ähnlich wie bei der Diagnostik des Reizdarmsyndroms ("irritable bowel syndrome (IBS)") vorzugehen [52]. Hier werden die Beschwerden anhand definierter Diagnosekriterien (ROME IV criteria) zunächst in Obstipationsund Diarrhö-artige Symptome eingeteilt; anschließend erfolgt eine differenzialdiagnostische Abklärung möglicher Ursachen (die zugegebenermaßen mannigfaltig sind).…”
Section: Funktionelle Darmproblemeunclassified
“…Zu langfristigen Darmbeschwerden nach radikaler Zystektomie gibt es wenig validierte Daten, entsprechend liegen auch speziell für diese Situation keine evidenzbasierten Empfehlungen für eine mögliche Therapie vor. Ein möglicher Ansatz ist es, bei den Patienten, die durch funktionelle Darmbeschwerden belastet sind, ähnlich wie bei der Diagnostik des Reizdarmsyndroms ("irritable bowel syndrome", IBS) vorzugehen [52]. Hier werden die Beschwerden anhand definierter Diagnosekriterien (ROME IV criteria) zunächst in Obstipations-und Diarrhö-artige Symptome eingeteilt; anschließend erfolgt eine differenzialdiagnostische Abklärung möglicher Ursachen (die zugegebenermaßen mannigfaltig sind).…”
Section: Funktionelle Darmproblemeunclassified